Doing Philosophy: - Schick, Theodore (GcGraw-Hill, 2003)
Doing Philosophy helps students understand the nature and purpose of philosophical inquiry by explaining what philosophical problems are, how they can be solved, and why searching for solutions is important. By acquainting students with philosophical theories and the thought experiments used to test them, this text fosters active learning and helps students become better thinkers.